Correction: Integrated different forms of business communication by using internet telephony (2017, vol.5, no.2, str.29-35) - Bjelobaba Goran; Savić Ana; Stefanović Hana (Trendovi u Poslovanju)
The paper provides an overview of development and use of Internet technologies in improving business by integrating different types of communication. The advantages of using the standard open IP - Internet Protocol in establishing integrated communication are presented as some of the potential possibilities of upgrading the existing conventional telephone network. The paper presents a concrete implementation of internet telephony in business premises in order to reduce operating costs, as well as the analysis of the possibilities of applying new multimedia applications and services by using a single integrated network. Comparison of performance of the original, sent speech signal and the received speech signal, after passing through the IP network, for different values of packet loss rate is analyzed.